Multimedia Textbook: German for Mechanical Engineering - Tomankova, Anna; Gallova, Sona (Communications - Scientific letters of the University of Zilina, 2013)
In our presentation we would like to inform about the international project DEUMA called “German for Mechanical Engineering”. This project was supported by the European Union as part of LEONARDO DA VINCI II program in which 11 partners from 5 countries participated. The aim of the project was to create a multimedia textbook of technical German language that would be designed especially for students of Faculties of Mechanical Engineering as well as for other students of German language with the focus on its use in the field of professional engineering. DEUMA teaching materials are modern multimedia language tools helping to improve professional German language knowledge in the field of mechanical engineering for Czech, Slovak and French students, teachers and practitioners in the field. The Internet and CD ROM versions enable both self-study and “blended learning” as a combination of classroom teaching and e-learning.